Patient Perspectives on Benign Prostatic Hyperplasia Surgery: A Focus on Sexual Health. Issue 10 (6th August 2020) - Bouhadana, David; Nguyen, David-Dan; Zorn, Kevin C.; Elterman, Dean S.; Bhojani, Naeem
Abstract: Background: In the last decade, many novel minimally invasive surgical techniques within benign prostatic hyperplasia (BPH) surgery were developed to reduce postoperative complications that often discourage patients from pursuing BPH surgery. Aim: To assess perspective of future and past international BPH surgery patients regarding their postoperative complications, namely erectile and ejaculatory function. Methods: A survey was distributed randomly to 2 groups of BPH patients: one with 149 patients having undergone surgery in the last 2 years (group A), and the other cohort of 151 men seriously considering BPH surgery in the next year (group B). This survey consisted of 20 questions that assessed patients' motivating factors for undergoing elective BPH surgery and their perspectives regarding the potential postoperative complications attributed to BPH surgery. Outcomes: The perspective of future and past international BPH surgical patients towards the preservation of their erectile and ejaculatory functions was assessed with the help of a survey. Results: Results indicated that in general BPH surgery patients considered the maintenance of erectile (95%, n = 284) and ejaculatory function (92%, n = 276) to be important preoperative considerations, regardless of their age. Patients aged 50–59 years were most concerned with the permanent impact on sexual function and patients aged >60 years were most concerned with urinary incontinence. In patients aged >70 years, 66% (n = 43) and 62% (n = 40) of the respondents indicated that maintaining erectile and ejaculatory function was important, respectively. Clinical Implications: Patient-centered care needs to be implemented in order to address the importance that past and future BPH surgery patients hold toward the maintenance of their postoperative sexual function. Strengths & Limitations: In the group of patients having previously undergone BPH surgery, the possibility of recall bias should be taken into account when interpreting the study's findings. However, maintaining sexual function was also important for the group of patients seriously considering surgery in the next year suggesting that these considerations are not solely due to recall bias. Additionally, the results were limited by the small sample size of participants in groups A (n = 149) and B (n = 151). Conclusion: It was found that past and future BPH surgery patients attribute a significant importance toward the maintenance of their sexual function. Although novel approaches with better sexual outcomes such as Rezum and UroLift for prostates <80 mL, and Aquablation for any size prostate are available, more research is needed to investigate their long-term effects on sexual function before they can be recommended to patients.